PENGARUH KUALITAS PELAYANAN DAN HARGA TERHADAP KEPUASAN PELANGGAN PADA JASA PERCETAKAN DI LINGKUNGAN SEKITAR KAMPUS STIE BHAKTI PEMBANGUNAN - Parmin, Yohanes (Sekolah Tinggi Ilmu Ekonomi Bhakti Pembangunan, 2025)
The purpose of this study is to determine the influence of Service Quality and Price on CustomerSatisfaction with Printing Services located around STIE Bhakti Pembangunan. The subjects in thisresearch were consumers who ordered prints at printing shops around STIE BhaktiPembangunan. The independent variables in this research are Service Quality (X1) and Price (X2)with the dependent variable being Customer Satisfaction (Y). From the results of the t test analysiswith a significance level of 5%, it shows that Service Quality is 0.015, and Price is 0.018. The resultsof the F test show that simultaneously or simultaneously the variables Service Quality and Pricehave an influence on Customer Satisfaction with the calculated F value obtained at 103.367. Thevalue in the Coefficient of Determination (R2) test is 0.858. This figure shows that CustomerSatisfaction can be explained by the Service Quality and Price factors at 85.8%, while theremaining 14.2% is explained by other factors which are likely to have a greater influence on thePrinting Services that grow around the STIE Bhakti Pembangunan campus.